Creatine kinase-MB elevation in patients with acute aortic dissection predict worse in-hospital outcomes - Yijing Xin; Siqi Lyu; Yanmin Yang (International Journal of Cardiology: Heart & Vasculature)
Background: The aim of this study was to evaluate the association between baseline creatine kinase-myocardial band (CK-MB) and the risk of in-hospital all-cause mortality in acute type A and type B aortic dissection (AD) patients, and to explore the predictive value of CK-MB. Methods: A single-center retrospective analysis was performed on 552 acute AD (type A 329 patients, type B 223 patients). Outcomes were the incidence of in-hospital all-cause mortality. Kaplan-Meier curve was used to compare the all-cause death risk in two groups (normal CK-MB group and elevated CK-MB group). The Cox regression model and restricted cubic splines (RCS) were conducted to assess the relationship between CK-MB and outcomes. Stratified analysis was performed based on gender, age (<50 years or ≥ 50 years), and surgery or endovascular therapy. Results: The Kaplan-Meier curves showed statistically significant differences in outcomes among the different CK-MB level groups for both acute type A and type B AD patients. Cox regression analysis revealed that the in-hospital mortality risk was significantly high in the elevated CK-MB groups for both acute type A and type B AD patients. The RCS curve revealed that CK-MB was non-linearly and J-shaped correlated with in-hospital all-cause mortality for acute type A AD patients, and linearly correlated with in-hospital all-cause mortality for acute type B AD patients. Conclusion: Baseline CK-MB elevations were associated with an increased risk of in-hospital all-cause mortality in acute type A and type B AD patients, and it was independently associated with poor prognosis in type A patients.